Keaktifan Orang Muda Katolik Dalam Tugas Liturgi Di Gereja Santo Yosep Stasi Lubuk Mantuk - Tryepina Paulina Nona; Intansakti Pius X (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
Young Catholics have an important role to play in the Church as the next generation and agents of change. This was affirmed by Saint Yoanes Paul II who called them the future of the Church and a source of hope for society. The Church sees the importance of the physical and spiritual development of young Catholics so that they are ready to take part in the service of the Church. The active participation of the faithful, especially the youth, is essential in realizing the expectations of all Church members in seeing the Church flourish. Young Catholics are encouraged to participate in various church activities, which aim to awaken their enthusiasm in knowing and deepening the Christian faith. The Church is expected to give attention and care in the apostolic task so that young people can live their faith. Liturgy as a work or service for the nation and a celebration of the mystery of salvation from God through Jesus Christ, plays an important role in shaping the faith and positive values of young people. This study aims to find out the participation of Catholic Youth in liturgical duties at St. Joseph's Church Stasi Lubuk Mantuk and identify the factors that cause their lack of participation. This study confirms that the responsibility of building the spirit of youth is the duty of the Church and the whole community